2021
DOI: 10.1093/abm/kaab051
|View full text |Cite
|
Sign up to set email alerts
|

Minority Stress, Structural Stigma, and Physical Health Among Sexual and Gender Minority Individuals: Examining the Relative Strength of the Relationships

Abstract: Background Sexual and gender minority (SGM; i.e., non-heterosexual and transgender or gender-expansive, respectively) people experience physical health disparities attributed to greater exposure to minority stress (experiences of discrimination or victimization, anticipation of discrimination or victimization, concealment of SGM status, and internalization of stigma) and structural stigma. Purpose To examine which components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Structural stigma is conceptualized as the social conditions, cultural norms, and institutional policies that detract from the wellbeing of marginalized communities, including SGM people [21]. Research has primarily examined structural stigma as directly impacting SGM people's health [22][23][24][25][26], but structural stigma also limits access to high-quality social resources [27], such as healthcare. SGM people living in areas with high structural stigma (i.e., U.S. Census regions with more anti-SGM policies) are less likely to access healthcare [28] and more likely to report lower-quality care [29].…”
Section: Structural Stigma and Government Funding As Structural Deter...mentioning
confidence: 99%
“…Structural stigma is conceptualized as the social conditions, cultural norms, and institutional policies that detract from the wellbeing of marginalized communities, including SGM people [21]. Research has primarily examined structural stigma as directly impacting SGM people's health [22][23][24][25][26], but structural stigma also limits access to high-quality social resources [27], such as healthcare. SGM people living in areas with high structural stigma (i.e., U.S. Census regions with more anti-SGM policies) are less likely to access healthcare [28] and more likely to report lower-quality care [29].…”
Section: Structural Stigma and Government Funding As Structural Deter...mentioning
confidence: 99%
“…Our findings show that more protective policy environments are associated with greater reports of past-year discrimination and victimization among cisgender SM people and gender expansive GM people. Discrimination is associated with a wide range of disparities, including poor mental [ 58 , 59 ] and physical health outcomes [ 60 , 61 ] and with delays in seeking healthcare services [ 11 , 62 ]. Further research should examine whether policy environments moderate the relationship between reported discrimination and victimization and the health of SGM people.…”
Section: Discussionmentioning
confidence: 99%
“…Social acceptance of MSM is variable across nations and cultures. [ 7 8 9 ] In America, social marketing has played a major role in social acceptance of gay, lesbian, bisexual and transgender people. Compared to a decade earlier, 60% of Americans are more likely to accept gay relationships and marriages.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Social and family acceptance and safe community environment have strong association with improved health conditions. [ 8 9 ] Fear of anticipated discrimination and disparity in access to health facilities is an universal phenomenon. [ 10 11 12 13 ] The ongoing COVID-19 pandemic has made the gender minority population more vulnerable.…”
Section: Introductionmentioning
confidence: 99%